Alterations of Regional Homogeneity in Children With Congenital Sensorineural Hearing Loss: A Resting-State fMRI Study - Guo, Pingping; Lang, Siyuan; Jiang, Muliang; Wang, Yifeng; Zeng, Zisan; Wen, Zuguang; Liu, Yikang; Chen, Bihong T. (Frontiers in Neuroscience, 2021)
Background: Brain functional alterations have been observed in children with congenital sensorineural hearing loss (CSNHL). The purpose of this study was to assess the alterations of regional homogeneity in children with CSNHL. Methods: Forty-five CSNHL children and 20 healthy controls were enrolled in this study. Resting-state functional MRI (rs-fMRI) parameters for regional brain homogeneity such as Kendall coefficient consistency (KCC-ReHo) and coherence-based regional homogeneity (Cohe-ReHo) were analyzed and compared between the two groups, i.e., children with CSNHL and the healthy controls. Results: Compared to the healthy controls, CSNHL children showed an increased Cohe-ReHo values in left calcarine, and decreased values in bilateral ventrolateral prefrontal cortex (VLPFC), and right dorsolateral prefrontal cortex (DLPFC). CSNHL children also had increased KCC-ReHo values in left calcarine, cuneus, precentral gyrus and right superior parietal lobule (SPL), and decreased values in left VLPFC and right DLPFC. Correlations were detected between the ReHo values and the age of the CSNHL children. There were positive correlations between the ReHo values in the precuneus/PFC regions and age (p<0.05). There were negative correlations between ReHo values in bilateral temporal lobes, or fusiform gyrus, or parahippocampal gyrus or precentral gyrus and age (p < 0.05). Conclusions: CSNHL children had alterations of ReHo in the auditory, visual, motor and other related cortices as compared to healthy controls. There were significant correlations between age and the ReHo values in brain regions for information integration and processing. Our study showed promising data using rs-fMRI ReHo analysis to assess the brain functional alterations in children with CSNHL.